Anionic reverse microemulsion grafting of acrylamide (AM) on HydroxyEthylCellulose (HEC): Synthesis, characterization and application as new ecofriendly low-cost flocculant. (October 2019) - Chaouf, Sara; El Barkany, Soufian; Jilal, Issam; El Ouardi, Youssef; Abou-salama, Mohamed; Loutou, Mohamed; El-Houssaine, Ablouh; El-Ouarghi, Hossain; El Idrissi, Abderahmane; Amhamdi, Hassan
Abstract: New water-soluble cellulosic derivative based on HEC was successfully elaborated (HECc), and used as anionic coagulant-flocculant of colloidal systems Fe(OH)3 and to remove of heavy metal ions (Cu(II)) from aqueous media. HECc was synthesized in unconventional reverse microemulsion process using water as ecofriendly solvent and as hydrogen transfer agent, where cyclohexane was employed as continuous phase to reduce the hydrophobicity of the medium. The amide groups grafted on HEC main chain were saponified to increase the negative charge density, and then the zeta potential value of HECc derivative reached -45 mV. The proposed structure of HECc was confirmed by FTIR, 1 H, 13 C NMR and deept-135. The XRD technique was used to study the effect of grafting process on the crystalline order. Moreover, the morphological changes and the elementary composition of the surfaces were studied using scanning electron microscope equipped with EDX. The new HECc coagulant-flocculant showed a high coagulation-flocculation capacity toward Fe(OH)3 colloidal system at 35 μL as added volume of 0.5% flocculant solution. Moreover, the pH values showed an important effect (species distribution) on the coagulation-flocculation mechanism and on the flocculating capacity to remove (Cu (II).